Sustainable processing of algal biomass for a comprehensive biorefinery - Javed, Muhammad Uzair; Mukhtar, Hamid; Hayat, Muhammad Tahir; Rashid, Umer; Mumtaz, Muhammad Waseem; Ngamcharussrivichai, Chawalit (Elsevier, 2022)
Nearly 15 billion metric tons of fossil fuels are consumed each year all over the world resulting in the depletion of non-renewable energy resources day by day therefore in the coming years, the shortage and price hikes of these fuels are inevitable. On the other hand, the global energy demand is projected to rise by almost 28% by 2040 compared to current levels. Thus, there is a dire need for developing the alternatives to meet these energy needs. Biomass is seen as a significant alternative energy source to fossil fuels from this standpoint. The main bottle neck in utilizing the biomass for this purpose is the lack of an efficient conversion or pretreatment technology which prompted scientists to delve into novel stepwise biomass conversion technologies. This review article encompasses various methods for the processing the algal biomass to generate potential biobased products such as algal crude oil, biogas, and fuel alcohols. Among the various techniques of thermochemical conversion of algal biomass, hydrothermal liquefaction and gasification are the most sustainable ones. Furthermore, anaerobic digestion of lignocellulosic biomass is the commercially workable technique providing biogas and biohydrogen. Future generations may find algal biofuels to be low-cost and ecologically benign alternative to fossil fuels. This review is a connotative illustration of the conversion technologies for algal biomass, which includes both thermochemical and biochemical processes. It also highlights the salient features along with the limitations of each of these technologies and bearing in mind the expansion of a superstructure depiction to capture the various biomass feedstocks and employment techniques for the generated bioenergy through various biomass conversion technologies.